2010
DOI: 10.1111/j.1750-3841.2010.01604.x
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Removal of Caffeine from Green Tea by Ultrasonic‐Enhanced Supercritical Fluid

Abstract: Low-caffeine or caffeine-removed tea and its products are widely welcomed on market in recent years. In the present study, we adopt ultrasonic-enhanced supercritical fluid extraction process to remove caffeine from green tea. An orthogonal experiment (L16 (4(5))) was applied to optimize the best removal conditions. Extraction pressure, extraction time, power of ultrasound, moisture content, and temperature were the main factors to influence the removal rate of caffeine from green tea. The 5 factors chosen for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Due to its high selectivity for CAF, this method has been tested in several studies to separate CAF from catechins (Huang, Wu, Chiu, Lai, & Chang, ; Kim, Kim, Kim, Oh, & Lee, ; Park et al., ). Tang, Li, Lv, and Jiang () used SCCO 2 as cosolvent with the aid of ultrasound. CAF recovery in their study was around 79%.…”
Section: Extraction and Separation Of Egcgmentioning
confidence: 99%
“…Due to its high selectivity for CAF, this method has been tested in several studies to separate CAF from catechins (Huang, Wu, Chiu, Lai, & Chang, ; Kim, Kim, Kim, Oh, & Lee, ; Park et al., ). Tang, Li, Lv, and Jiang () used SCCO 2 as cosolvent with the aid of ultrasound. CAF recovery in their study was around 79%.…”
Section: Extraction and Separation Of Egcgmentioning
confidence: 99%
“…Green tea also contains about 1-5% caffeine (dry weight basis), which is considered to exert health problems, such as sleep deprivation and hypersensitivity (Hindmarch et al, 2000;Masdrakis et al, 2009). Several methods have been suggested to remove caffeine from green tea extracts, including organic solvents extraction, water extraction, supercritical carbon dioxide extraction, ultrasonic-enhanced supercritical fluid and recent microwave-enhanced vacuum ice water extraction (Perva-Uzunalic et al, 2006;Kim et al, 2008;Tang et al, 2010;Lou et al, 2012). In general, the decaffeination processes may reduce the amount of catechins in tea, so it might not provide the same health benefits as caffeinated green tea (Henning et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is described that EGCG/Caffeine level was higher in ultrasound-assisted extraction by immersed ultrasonic bath than that in water extraction by heated magnetic stirrer. Tang also reported that ultrasonic-enhanced supercritical fluid extraction was effective at removing caffeine from green tea without damaging the structure of its active components [45]. However, this technique has some defects such as long extraction time (4 h) and high extraction pressure (30 MPa), resulting in high operating costs and limiting its large-scale industrial application.…”
Section: Resultsmentioning
confidence: 99%